1994
DOI: 10.1099/00222615-41-3-204
|View full text |Cite
|
Sign up to set email alerts
|

An in-vitro study of the sterol content and toxin production of Fusarium isolates from mycotic keratitis

Abstract: Summary.Isolates of Fusarium species from 18 patients with keratomycosis were examined for their C-29 and C-31 sterol content and for their capacity to synthesise mycotoxins. All isolates were resistant to azole antifungal agents in vitro and the sterol contents were indistinguishable. In-vitro toxin production was monitored by gas chromatography-mass spectrometry ; 13 isolates produced nivalenol, six produced deoxynivalenol, nine gave T-2 toxin and two showed the presence of diacetoxyscirpenol at different ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
1
9
1
1
Order By: Relevance
“…In harmony with our results, Raza et al . [24] found that isolates of Fusarium species from 18 pateints with keratomycosis could produce mycotoxins in vitro . Of these isolates, 13 produced nivalenol, 6 produced deoxynivalenol, 9 gave T-2 toxin, and 2 showed the presence of diacetoxyscirpenol at different intervals.…”
Section: Discussionmentioning
confidence: 99%
“…In harmony with our results, Raza et al . [24] found that isolates of Fusarium species from 18 pateints with keratomycosis could produce mycotoxins in vitro . Of these isolates, 13 produced nivalenol, 6 produced deoxynivalenol, 9 gave T-2 toxin, and 2 showed the presence of diacetoxyscirpenol at different intervals.…”
Section: Discussionmentioning
confidence: 99%
“…are known to cause myelosuppression through toxin production (263), but little is known about whether Fusarium toxins such as nivalenol, T-2 toxin, deoxynivalenol, diacetoxyscirpenol and fusaric acid contribute to the pathogenesis of mycotic keratitis ( Table 9). The results of two studies (316,383) suggest that these factors do not make any such contribution, but further investigation is required.…”
Section: Putative Agent Factors In the Pathogenesis Of Mycotic Keratitismentioning
confidence: 98%
“…Several toxins produced by Fusarium spp. include nivalenol, T-2 toxin, deoxynivalenol, diacetoxyscirpenol and fusaric acid [157] studied the relationship of toxin production with the severity of disease and concluded that toxin production in vitro did not relate to the clinical presentation of severity of keratitis and the outcome of the treatment. The toxic effects of aflatoxins on the cornea of chicks has been established [86].…”
Section: Toxigenicitymentioning
confidence: 99%